Plant medicines in respiratory tract disease – STANce of the Polish Phytotherapy Association – STANFITO I - Doniec, Zbigniew; Krauze-Baranowska, Mirosława; Czerwionka-Szaflarska, Mieczysława; Kuchar, Ernest; Fecka, Izabela; Sybilski, Adam; Woroń, Jarosław; Mastalerz-Migas, Agnieszka (Lekarz POZ, 2024)
Acute respiratory infections are the most common reason to seek medical attention in primary care. The infections are mostly of viral aetiology, and preparations containing herbal substances are used in symptomatic treatment. This paper reviews single and combination herbal medicinal products used for dry and wet cough. The therapeutic effects of individual plant substances are discussed regarding the presence of specific biologically active compounds, taking into account the results of clinical application studies.